Serang Regency Infrastructure Service Satisfaction Index - Mahmud Ali; Maulana, Rachmat; Hakim, Agus Lukman; Andayani, Nopi; Ali Ramdhani, Miftah Faiz; Hanifah, Hanifah; Yuniar , Siti; Haryo Setyoko (Sean Institute, 2024)
To measure the level of public satisfaction with public services, an evaluation of the quality of public service delivery is needed, one of which is infrastructure in Serang district (highways, bridges, land transportation, agricultural irrigation, clean water infrastructure and housing/settlement services). This study was conducted to measure the level of customer satisfaction (community) with public services in the field of infrastructure provided by the Regional Apparatus of Serang Regency, Banten Province. The methods used in this study are descriptive, exploratory, survey and evaluation research methods and with a non-experimental quantitative approach. The sample of this study was 96 respondents divided into 3 regional clusters, and the sampling technique used was a non-probability sampling technique with a type of purposive side combined with accidental sampling techniques. Data analysis techniques used in this study include validity tests, reliability tests, univariate analysis, and Importance Performance Analysis (IPA). The results of this study showed that a univariate analysis of infrastructure services (roads, bridges, land transportation, agricultural irrigation, clean water infrastructure and housing services) in Serang Regency obtained an average score of 78.54 with good service unit performance. The results showed that the Importance Performance Analysis (IPA) method obtained the results of 30 questions that became priorities for improvement, namely being in quadrant I (high importance while low satisfaction) with 9 questions. In this case, the Serang Regency Government should make improvements to services that prioritize services that have a high level of importance but low satisfaction, namely land transfortation services, agricultural irrigation, and housing/settlement services.